Case report: A case of hypocalcemic cardiomyopathy with non-reversible cardiac fibrosis - Xie, Ying; Yang, Jing; Li, Kun; Liu, Fang; Yi, Yi; Zhang, Ping (Frontiers in Cardiovascular Medicine, 2023)
Hypocalcemic cardiomyopathy is a rare etiology of heart failure. It is considered highly reversible with a relatively favorable prognosis. This case reports a 52-year-old housewife diagnosed with hypocalcemic cardiomyopathy who presented with acute decompensated heart failure and hypocalcemia symptoms with a history of thyroidectomy. Shortness of breath and edema were relieved after diuresis and prompt electrolyte correction. The left ventricular ejection fraction increased from 27% to 53%, and the left ventricular end-diastolic dimension shortened from 58 to 50 mm in echocardiographic re-examinations, while repeat cardiac magnetic resonance imaging revealed evidence of non-reversible cardiac fibrosis after 1-year follow-up. Cardioprotective agents with close follow-ups were called for in this entity of patients.